Employee Development Management Practices and Their Role in Enhancing Government Institution Work Performance: A Qualitative Study - Setiawan, Didy; Subiyantoro, Subiyantoro; Prastica, Dynar Vivian; Rohmah, Wafiq Nur Ziyadatur (Jurnal Ilmiah Manajemen & Bisnis, 2023)
This research aims to reveal how the concept of employee development management implemented by BPMP DI Yogyakarta optimizes work performance during the COVID-19 pandemic. The pandemic has necessitated that all activities be conducted online, which has created some impediments to employee development, such as instability of the internet network, passive participants, and distractions in the participant environment. This qualitative study uses purposive sampling to select subjects who are knowledgeable, experienced, and understanding of the research theme. Employee development programs at BPMP DI Yogyakarta include institutional development, career development, and education and training. The program has been implemented properly and accurately through the implementation of management functions, including planning, organizing, actuating, controlling, and evaluating. The role of employee development management is illustrated by the increase in the achievement of the SAKIP value of BPMP DI Yogyakarta by 7.9 points in the 2019-2021 period. Additionally, BPMP DI Yogyakarta achieved the ZI-WBK predicate in 2020. These two achievements demonstrate that the employee development management carried out by BPMP Yogyakarta is effective and has successfully optimized employee and institutional performance during the COVID-19 pandemic.